Transgeneridade e cárcere: preconceito e binarismo no sistema prisional brasileiro - Pereira, Marianne dos Reis (2022)
The present dissertation proposes a research on the prejudice against transgender people in a situation of deprivation of liberty in Brazil. The theme will be approached from the emergence of the gender category in the historical context of the feminist movement, focusing on the issue of transphobia, the imposition of the heterosexual norm and the depathologization of trans identity. A conceptual and historical contextualization of the dignity of the human person and its affirmation as the foundation of the Brazilian Democratic State is carried out, highlighting the need for its implementation within the scope of the penal system, notably from the perspective of sexual diversity. The research has a qualitative approach and was carried out through a bibliographic and documental review on the subject. The study seeks to highlight the hermeneutical lack of the country in protecting the fundamental rights of this minority portion of the population, allocated in environments based on sexual binarism, alluding to the public policies adopted, aiming to reduce discrimination against this public, to, in the end, highlight the role of the Judiciary in the realization of the rights of LGBTI people deprived of their liberty in Brazil